2007
DOI: 10.1128/jvi.00013-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Alpha/Beta Interferon Response by Mouse Hepatitis Virus at Multiple Levels

Abstract: Coronaviruses are a family of large positive-sense RNA viruses that are responsible for a wide range of important veterinary and human diseases. Coronaviruses are divided into three groups, with group I and II viruses infecting mammals and group III viruses infecting avian species (76). Human coronaviruses (HCoV), such as the group I HCoV-229E and group II HCoV-OC43 viruses, cause approximately 5 to 30% of all human respiratory tract infections (76, 77). In late 2002, severe acute respiratory syndrome-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
117
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 85 publications
17
117
0
Order By: Relevance
“…Furthermore MHV displays cell-type specific sensitivity to the antiviral effects of IFN treatment, with macrophage lineage cells being most successful in restricting MHV replication (Rose and Weiss, 2009; Zhao et al, 2011). We also observed that MHV was unable to prevent IFN induction by a co-infecting virus and was also unable to protect a co-infecting virus from the effects of IFN (Roth-Cross et al, 2007). Thus, we reasoned that MHV is unable to subvert major IFN signaling pathways, but rather may interfere with one or more IFN induced antiviral activities.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore MHV displays cell-type specific sensitivity to the antiviral effects of IFN treatment, with macrophage lineage cells being most successful in restricting MHV replication (Rose and Weiss, 2009; Zhao et al, 2011). We also observed that MHV was unable to prevent IFN induction by a co-infecting virus and was also unable to protect a co-infecting virus from the effects of IFN (Roth-Cross et al, 2007). Thus, we reasoned that MHV is unable to subvert major IFN signaling pathways, but rather may interfere with one or more IFN induced antiviral activities.…”
Section: Resultsmentioning
confidence: 98%
“…We found that LCMV replicated similarly in ST-NP ϫ Deleter and in wild-type macrophages (data not shown). It has been suggested that ubiquitous and constitutive endogenous expression of LCMV-NP interferes with IFN-␣ production (28,29), which is crucial for immediate virus control (30). IFN-␣ levels were measured in the sera 12, 24, and 48 h after high-dose LCMV infection, and no difference between NP-tolerant and control mice was found (data not shown), excluding impaired IFN-␣ production as crucial factor for the observed difference in viral clearance between control and ST-NP ϫ Deleter mice.…”
Section: Discussionmentioning
confidence: 99%
“…). JHM viruses are known to proliferate, suppressing the production of IFN‐β in the in vitro ‐infected cells . Because IFN‐β levels in the pons were increased after infection both in mutant and wild‐type mice, we examined IFN‐β expression by immunofluorescence, and IFN‐β was found to be widely distributed in the brain parenchyma, where viral antigens were not detected at 48 hpi, although many infected cells had infiltrated the meninges, as shown in the upper left corner of Fig.…”
Section: Resultsmentioning
confidence: 99%